Should One Assume the Discount Rate to Be One of the Risk Factors? - Kaczmarzyk, Jan (Czy powinniśmy zakładać, że stopa dyskontowa jest jednym z czynników ryzyka?, 2023)
The Monte Carlo simulation is the ultimate solution for considering nearly all possible scenarios in presumably any discounted cash flow valuation. This paper argues that a discount rate expresses an investor’s current requirement and should be respectively perceived as a parameter only. The consequences of qualifying a required rate of return (a discount rate) as a risk factor in a discounted cash flow valuation are described in the paper using a free cash flow financial model of an asset being a hypothetical publicly traded enterprise. The case study is a discounted cash flow valuation using the Monte Carlo simulation for risk analysis. The various sets of assumptions are considered to explain the consequences of qualifying a required rate of return in a discounted cash flow model as a risk factor. As indicated in the paper, the discount rate as an additional risk factor with an attributed probability distribution increases the volatility of a risk variable, then the distribution of a risk variable becomes more flattened. In previous studies, some authors indicated that a discount rate could be considered a risk factor in the Monte Carlo simulation (Krysiak 2000; Damodaran 2018).
Financial Sciences. Nauki o Finansach, 2023, vol. 28, no. 2, s. 1-10
Keywords: corporate finance; valuation; DCF; risk analysis; Monte Carlo simulation; finanse przedsiębiorstwa; analiza ryzyka; wycena; Monte Carlo